OPTIMALISASI DIGITAL MARKETING SEBAGAI STRATEGI PROMOSI KREATIF UNTUK PEMBERDAYAAN UMKM DI KELURAHAN KEDUNG BARUK KOTA SURABAYA - Wulandari, Indah Sholihah; Bagaskara, Ramadani Teja; Febrianita, Roziana (STAI Darul Qalam Tangerang, 2025)
The Community Service Program (KKN) in Kedung Baruk Village, Surabaya City, focused on empowering Micro, Small, and Medium Enterprises (MSMEs) through creative and visually appealing promotional strategies. MSMEs in this region have significant potential to support local economic growth, but still face obstacles in reaching a wider market due to limitations in product promotion and branding. Many have not yet utilized powerful digital and visual media as effective marketing tools. Through this KKN program, students act as mentors and facilitators in developing promotional strategies based on visual design, simple digital marketing, and strengthening product identity. These steps included training in packaging design, creating promotional content for social media, and mentoring in building brand image. The results of this activity indicate an increase in the understanding and skills of MSMEs in promoting their products in a more attractive and professional manner. With a creative approach relevant to current market needs, it is hoped that MSMEs in Kedung Baruk Village can grow more independently, be highly competitive, and have the ability to continuously innovate in developing their businesses. This activity demonstrates that collaboration between students and the community can have a tangible impact on local economic progress.